Texas Root-Knot Nematode Meloidogyne haplanaria Eisenback et al. 2003 (Nematoda: Chromadorea: Chromadoria: Rhabditida: Rhabditina: Tylenchomorpha: Meloidogynidae) - Alemayehu Habteweld; William T. Crow (EDIS)
Includes: Introduction - Distribution - Life Cycle and Biology - Hosts - Economic Importance - Management - Selected References.